Insights, innovation, and analytics for optimal customer engagement - Nagaraj, Samala, 1980- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"This book is an attempt to study the emerging concept of customer engagement and investigating underlying theories, innovative ways, review of existing literature, engagement analytics and insights for marketers with reference to customer engagement"--